Performance of a zero-inertia model for irrigation with rapidly varied inflow discharges - Liu, Kaihua; Jiao, Xiyun; Li, Jiang; An, Yunhao; Guo, Weihua; Salahou, Mohamed Khaled; Sang, Honghui (International Journal of Agricultural and Biological Engineering, 2020)
The zero-inertia model is widely used for simulating surface flow in irrigation systems. This model is accurate when inflow discharge is constant. However, simulation of irrigation systems with rapidly varied inflow discharge is needed due to the development of real time control irrigation technology. Hence, the objective of this study is to validate the zero-inertia model with rapidly varied inflow discharge. For this purpose, twenty-three border irrigation tests at a range of inflow changes on different field slopes and roughness coefficients were conducted. Then, the sensitivity analyses of bed slope, infiltration parameters, and roughness coefficient were examined. The results indicate that the zero-inertia model predictions are in good agreement with field data in both advance/recession times and flow depths. The infiltration parameters were the most sensitive input variable of the zero-inertia model. The input variables have a more considerable impact on the recession phase than the advance phase. Keywords: zero-inertia model, rapidly varied inflow, border irrigation, sensitivity analysis DOI: 10.25165/j.ijabe.20201302.5228 Citation: Liu K H, Jiao X Y, Li J, An Y H, Guo W H, Salahou M K, et al. Performance of a zero-inertia model for irrigation with rapidly varied inflow discharges. Int J Agric & Biol Eng, 2020; 13(2): 175–181.